PREVALENCE OF GASTRO-INTESTINAL AND RESPIRATORY INFECTIONS IN LAKHIMPUR DISTRICT OF ASSAM, INDIA - Sharma, Jitendra (Innovare Journal of Life Sciences, 2014)
This study was carried out at Lakhimpur district in Assam, India for assessing the trend of gastroenteritis and respiratory disease. During the study, a large numbers of acute respiratory infections/influenza like illness (ARI/ILI) cases were observed which were closely followed by acute diarrhoea and bacillary dysentery. Most of the ARI/ILI cases were reported from Bihpuria block public health centre (BPHC). Incidence of acute diarrhoea and bacillary dysentery cases were high at Boginodi area. Beside this, high incidence of enteric fever cases was also reported in Lakhimpur district. The overall incidence was higher from May to June.